Bioactive compounds and antioxidant activity of germinated soybean flour (Glycine max L.) at different germination time - Hamidatun Hamidatun; Nabila Febriana; Giyatmi Giyatmi; Sudathip Sae-Tan; Dadi Hidayat Maskar (Agroindustrial Technology, University of Trunojoyo Madura, 2026)
Soybean (Glycine max L.) is a rich source of bioactive compounds, and germination is an effective process for improving its nutritional and functional properties. However, the combined effects of germination duration on sprout growth, bioactive compounds, and antioxidant activity in germinated soybean flour remain poorly understood. Therefore, this study aimed to evaluate the effect of different germination times on sprout growth, bioactive compounds, antioxidant activity, and proximate composition of germinated soybean flour. Soybeans were germinated for 0–7 days and analyzed for sprout growth, γ-aminobutyric acid (GABA), total phenolic content (TPC), total flavonoid content (TFC), antioxidant activity (DPPH), and proximate composition. Germination significantly affected all evaluated parameters (p 0.05). Sprout length increased continuously throughout germination, whereas GABA content reached its maximum on day 3 (416.43 ± 11.69 mg/100 g). The highest TPC (91.88 ± 1.20 mg GAE/100 g) and antioxidant activity (IC₅₀ = 10.57 ± 0.01 μg/mL) were obtained on day 5, while the highest TFC (17.30 ± 0.14 mg QE/100 g) was observed on day 4. Germination also increased protein, moisture, and ash contents while reducing fat content. These findings demonstrate that optimizing germination time effectively enhances the nutritional and functional quality of soybean flour, with 3–5 days representing the optimal germination period depending on the targeted bioactive compounds.